Electrocatalytic properties of perovskite-type La1-xSr xCoO3 (0≤x≤0.4) obtained by a novel stearic acid sol-gel method for electrocatalysis of O2 evolution in KOH solutions - Lal B.; Raghunandan M.K.; Gupta M.; Singh R.N. (My University, 2025)
Lanthanum cobaltate and its strontium-substituted products have been prepared using a novel stearic acid sol-gel method at 600 °C. The oxide catalysts followed the rhombohedral hexagonal crystal geometry. Sr-substitution (0.2-0.4 mol) increased the oxide roughness as well as the apparent electrocatalytic activity greatly. The oxygen evolution on each oxide catalyst showed two Tafel slopes, one (b1≅ 65 mV/decade) at low and the other (b2≅ 103 mV/decade) at higher overpotentials. The reaction order w. r. t. OH- concentration was approximately unity. Values of thermodynamic parameters for the oxygen evolution reaction (OER), namely, the standard enthalpy of activation (ΔH#0) and standard entropy of activation (ΔS#0) were ∼126kJmol-1 and ∼112Jdeg-1mol-1 and ∼109kJmol-1 and ∼144Jdeg-1mol-1 on the base oxide and La0.6Sr 0.4CoO3, respectively. © 2004 International Association for Hydrogen Energy. Published by Elsevier Ltd. All rights reserved.